Presidential Threshold in The Election of The President and Vice President from A Constitution and Human Rights Perspective - Sukadi, Imam; Jundiani, Jundiani; Bachri, Syabbul; Sinal, Mohamad; As-Suvi, Ahmad Qiram (Mimbar Keadilan, 2024)
Art 222 Law Number 7 year 2017 concerning General Elections, regulates the provisions of the threshold where the acquisition of seats in the DPR must be 20 percent or obtain valid votes nationally as much as 25 percent then political parties can nominate and nominate pairs of presidential and vice-presidential candidates. Setting the Presidential Threshold in the election of President and Vice President in Indonesia from a constitutional and human rights perspective brings its own problems in the Indonesian constitutional system. The Presidential Threshold system does give rise to privileges for certain parties. This is because only parties that meet the threshold can compete directly in the presidential election. It is for this reason that the privileges of these major parties have given birth to political cartels. What is bad for democracy is that it eliminates equal competition for all potential candidates to contest the Presidential election. The Presidential Threshold is not justified in eliminating or emasculating the meaning of democracy which provides rights and freedoms for citizens. Among the constitutional rights include the right to vote, the right to nominate (the right to be a candidate), and the right to nominate candidates, these are rights guaranteed by the 1945 Constitution of the Republic of Indonesia which everything is reduced because of this Presidential Threshold provision.